Analisa Manfaat dan Tantangan Implementasi Sistem Informasi Manajemen Aset Pada Institusi Pendidikan - Pawit Wahib; Ines Heidiani Ikasari (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2023)
Asset Management Information System (AMIS) has become a key element in asset management across various organizations, including educational institutions. Implementing AMIS in educational institutions can provide significant benefits such as asset management efficiency, improved inventory accuracy, and better maintenance. However, certain challenges can arise during the AMIS implementation process, which can affect its success. The research method used in this study is literature review. Literature review is a method used to gather, review, and analyze relevant literature or secondary sources related to the research topic. In this study, the author conducted a literature search through the website https://scholar.google.com, focusing on the implementation of Asset Management Information System (AMIS) in educational institutions. The author used relevant keywords such as "AMIS," "asset management," "implementation," and "educational institution" to search for literature relevant to the research topic. The analysis results indicate that implementing AMIS in educational institutions can provide significant benefits. The main benefits include improved efficiency in asset management, reduced operational costs, increased transparency in asset utilization, and improved scheduled maintenance. However, challenges in implementing AMIS in educational institutions also need to be considered. These challenges include organizational culture change, the need for adequate training for involved staff, integration with existing systems, and compliance with data security and privacy requirements.